Circulating Collagen Metabolites and the Enhanced Liver Fibrosis (ELF) Score as Fibrosis Markers in Systemic Sclerosis - Chen, Chen; Wang, Lingbiao; Wu, Jinfeng; Lu, Meijuan; Yang, Sen; Ye, Wenjing; Guan, Ming; Liang, Minrui; Zou, Hejian (Frontiers in Pharmacology, 2022)
Background: Serum fibrosis markers for systemic sclerosis (SSc) remain limited. The Enhanced Liver Fibrosis (ELF) score is a collagen marker set consisting of procollagen type III amino terminal propeptide (PIIINP), tissue inhibitor of metalloproteinases 1 (TIMP-1), and hyaluronic acid (HA). This longitudinal study aimed to examine the performance of the ELF score and its single analytes as surrogate outcome measures of fibrosis in SSc. Methods: Eighty-five SSc patients fulfilling the 2013 ACR/EULAR criteria with the absence of chronic liver diseases were enrolled. Serum PIIINP, TIMP-1, HA, and the ELF score were measured and correlated with clinical variables including the modified Rodnan skin score (mRSS) and interstitial lung disease (ILD). Twenty SSc patients underwent a follow-up serological testing and mRSS evaluation during treatment with immunosuppressants and/or anti-fibrotic drugs. Results: Serum PIIINP, TIMP-1, and ELF score were significantly higher in patients with SSc than in healthy controls (PIIINP: 10.31 [7.83-14.10] vs. 5.61[4.69-6.30], p<0.001; TIMP-1: 110.73 [66.21-192.45] vs. 61.81 [48.86-85.24], p<0.001; ELF: 10.34 [9.91-10.86] vs. 9.68 [9.38-9.99], p<0.001). Even higher levels of PIIINP, TIMP-1, and ELF score were found in patients with diffuse cutaneous SSc than those with limited cutaneous SSc. At baseline, both PIIINP and ELF score showed good correlation with mRSS (PIIINP: r=0.586, p<0.001; ELF: r=0.482, p<0.001). Longitudinal analysis showed that change in PIIINP positively correlated with change in mRSS (r=0.701, p=0.001), while change in ELF score were not related, in a statistical context, to the change in mRSS (ELF: r=0.140, p=0.555). Serum TIMP-1 was significantly higher in SSc patients with ILD, compared to the matched group of patients without ILD (109.45 [93.05-200.09] vs. 65.50 [40.57-110.73], p=0.007). Conclusions: In patients with SSc, the ELF score well correlates with the extent of skin fibrosis, while serum PIIINP is a sensitive marker for longitudinal changes of skin fibrosis. In the future, circulating collagen metabolites may potentially be used to evaluate therapeutic effects of anti-fibrotic treatments in the disease.